The notion of Mapuche “divinity”according to Sermón en lengua de Chile (1621) by Luis de Valdivia: an ethnocentric interpretation of indigenous otherness (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
Sermón en lengua de Chile (1621) written by Spanish Jesuit Luis de Valdivia incorporates vocabulary from the Mapudungun language. Several terms in Mapudungun such as ‗huecovoe‘, ‗marepuante‘ and ‗pillan‘, are explained as ―equivalents‖ of Christian divinities. Based on ethnohistorical studies, in this paper we analyze the effective concept relationships and meaning in the Mapuche culture. The main findings suggest that these concepts have undergone a semantic change as a result of the writer‘s worldviews. Thus, a fallible discourse is generated in its argument effectiveness.
Keywords: Sermons; Mapuche lexicon; Religion; Luis de Valdivia